Voluntary approaches to environmental protection: The role of legislative threats - Kathleen Segerson; Thomas J. Miceli (Fondazione Eni Enrico Mattei (FEEM), 1997)
Recently, attention has turned to the use of voluntary agreements between regulators and polluters as an alternative to mandatory approaches based on regulation or legislation. Voluntary agreements have the potential to reduce compliance costs by allowing greater flexibility and to reduce administrative and other costs. The purpose of this paper is to provide an economic model of the use of voluntary agreements where participation is induced through a background legislative threat. The goal is to determine whether a voluntary agreement is likely to be the outcome of the interaction between regulators and polluters, and the role that the legislative threat plays in determining that outcome. We consider first a model with a single firm and then extend the analysis to consider multiple firms. In the context of the single firm, we show that a mutually beneficial voluntary agreement always exists, but that the resulting level of abatement depends on the probability that legislation will be imposed. For the case of multiple firms, we examine the potential incentives for free-riding and ask how the terms of the agreement can affect these incentives. The results suggest that an increase in the magnitude of the threat (i.e., an increase in the probability that legislation would be imposed if a voluntary agreement is not reached) will generally increase the level of abatement under a voluntary agreement, and that if the probability of legislation is large enough, a first-best level of abatement is possible (though not guaranteed). In the context of multiple firms, the potential for free-riding can reduce the likelihood that a voluntary agreement will be reached.
Keywords: 330; Umweltrecht; Umweltpolitik; Selbstverpflichtung; Verhandlungen; Theorie